2018
DOI: 10.1021/acs.analchem.8b03124
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Imaging of Specific Proteins in the Human Retina by Laser Ablation ICPMS using Bioconjugated Metal Nanoclusters as Labels

Abstract: A sensitive methodology using antibody-conjugated gold nanoclusters (AuNCs) was developed for the quantitative bioimaging of specific proteins in biological tissues by laser ablation (LA) coupled to inductively coupled plasma-mass spectrometry (ICPMS). Determination of metallothioneins (MT1/2 protein isoforms) images in human retina tissue sections was carried out as a proof of concept. AuNCs used as label were conjugated to the selected antibody through carbodiimide coupling. A stoichiometry of AuNCs/availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…Although several studies can be found nowadays in the literature related to the imaging of biomolecules by LA-ICP-MS, most of them only collect qualitative distributions of sought proteins. In this context, we have recently proposed the use of small metal nanoclusters (NCs) with fluorescent properties as elemental labels for specific and absolute quantitative imaging of proteins in biological tissues by LA-ICP-MS [21,22]; considering that each NC has several hundreds of metal atoms, a high signal amplification in LA-ICP-MS measurements can be achieved. Therefore, these metal NCs offer possibilities for multimodal imaging (through fluorescence and MS analysis) in the same tissue section.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies can be found nowadays in the literature related to the imaging of biomolecules by LA-ICP-MS, most of them only collect qualitative distributions of sought proteins. In this context, we have recently proposed the use of small metal nanoclusters (NCs) with fluorescent properties as elemental labels for specific and absolute quantitative imaging of proteins in biological tissues by LA-ICP-MS [21,22]; considering that each NC has several hundreds of metal atoms, a high signal amplification in LA-ICP-MS measurements can be achieved. Therefore, these metal NCs offer possibilities for multimodal imaging (through fluorescence and MS analysis) in the same tissue section.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the dispersion associated to the AuNCs diameter, different experimental parameters were evaluated, starting from the previously synthesized AuNCs [6]. Briefly, the synthesis protocol was as follow: 20 mL of ultrapure water and 50 µ L of NaOH (2 M) were collected in a cylindric flask, then 6.3 mg of lipoic acid were added and, subsequently, the solution was stirred until complete dissolution.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the analysis of tissues and cells, the use of LA solid sampling technique allows to determine the sough proteins concentration and their distribution along the micrometer structures of the samples (lateral resolution in the range of 1-5 μm has been reported). In this case, AuNCs, AgNCs and PtNCs have been successfully investigated as elemental tags for proteins determination in human brain and ocular tissues [6][7][8]. However, the main limitation of using MNCs for quantification purposes is related to their size variability.…”
Section: Introductionmentioning
confidence: 99%
“…The Fernandez group reported a sensitive methodology to quantitatively determine metallothioneins (MT 1/2 protein isoforms) in human retina tissue sections by LA-ICPMS. 46 Au clusters are used as a label to provide a high amplification, which allowed conversion of 2D quantitative images of the distribution of MT 1/2 in the neurosensory retina layers by LA-ICPMS. The results were complementary to those determined using commercial ELISA kits ( Fig.…”
Section: Tumor Diagnosis With Metal Clustersmentioning
confidence: 99%